The relationship between albumin-bilirubin score and survival in patients operated for pancreatic cancer - Fidan, Evren; Yildirim, Atila; Kazaz, Nazli; Fidan, Sami; Cekic, Arif Burak (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate whether albumin-bilirubin score can be used as a prognostic marker in pancreatic cancer patients post-surgery. Method: The retrospective study was conducted at the Medical Oncology Clinic, Karadeniz Technical University, Trabzon, Turkey, and comprised data from 2010 to 2018 of pancreatic cancer patients who had undergone distal pancreatectomy or pancreaticoduodenectomy and were followed up for 3 years. Preoperative and postoperative serum albumin, carcinoembryonic antigen, carbohydrate antigen 19-9, bilirubin, neutrophil:lymphocyte ratio and platelet:lymphocyte ratio were compared as inflammation markers, while albumin-bilirubin scores were calculated using the equation linear predictor. Data was analysed using SPSS 17. Results: Of the 39 patients, 23(59%) were men and 16(41%) were women. The mean age of the sample was 62.4±10.2 years. No statistically significant changes were observed between preoperative and postoperative albumin-bilirubin scores, carcinoembryonic antigen, neutrophil:lymphocyte ratio and platelet:lymphocyte ratio (p>0.05). Significant decreases were observed in postoperative carbohydrate antigen 19-9, aspartate transaminase and alanine transaminas levels (respectively<0.05). No significant change was determined in postoperative albumin-bilirubin grade distributions compared to preoperative values (p=0.180). Although the rate of recurrence increased in line with preoperative albumin-bilirubin scores, the finding was not statistically significant (p=0.055). Mortality rate increased significantly in line with preoperative albumin-bilirubin scores (p=0.013). Conclusion: The albumin-bilirubin score affected survival in patients with pancreatic cancer, and can be employed as a prognostic factor in this patient group. Key Words: Pancreatic cancer, Albumin-bilirubin score, Prognostic factors.